Selective encapsulation of a chloride anion in a 1H-pyrazole Cu2+ metallocage. Issue 26 (28th June 2021) - Pitarch-Jarque, Javier; Jiménez, Hermas R.; Kalenius, Elina; Blasco, Salvador; Lopera, Alberto; Clares, M. Paz; Rissanen, Kari; García-España, Enrique
Abstract : A self-assembled metallobox from copper(ii ) and two macrocycles containing 1 H -pyrazole ligands encapsulates one chloride anion. Abstract : A self-assembled metallobox from copper(ii ) and two macrocycles containing 1 H -pyrazole ligands has been prepared. The internal cavity of the box is able to selectively encapsulate a single chloride anion over any other halide anion.